2016
DOI: 10.2147/ndt.s105478
|View full text |Cite
|
Sign up to set email alerts
|

Altered intrinsic regional brain spontaneous activity in patients with comitant strabismus: a resting-state functional MRI study

Abstract: ObjectiveTo investigate the underlying regional homogeneity (ReHo) of brain-activity abnormalities in patients with comitant strabismus (CS) and their relationship with behavioral performance.MethodsTwenty patients with CS (ten men and ten women) and 20 (ten men and ten women) age-, sex-, and education-matched healthy controls (HCs) underwent resting-state functional magnetic resonance imaging scans. The ReHo method was used to assess local features of spontaneous brain activities. Patients with CS were distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…The functional images were analyzed as described previously. 18 Briefly, the data were filtered by software and preprocessed using Statistical Parametric Mapping SPM8 (The MathWorks, Inc., Natick, MA, USA) and Data Processing Assistant for rs-fMRI DPARSFA (Institute of Psychology, CAS., Beijing, People’s Republic of China) software. 19 The first 10 volumes of each subject were discarded because of the signal reaching equilibrium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional images were analyzed as described previously. 18 Briefly, the data were filtered by software and preprocessed using Statistical Parametric Mapping SPM8 (The MathWorks, Inc., Natick, MA, USA) and Data Processing Assistant for rs-fMRI DPARSFA (Institute of Psychology, CAS., Beijing, People’s Republic of China) software. 19 The first 10 volumes of each subject were discarded because of the signal reaching equilibrium.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, the ReHo method has been successfully used to assess the neurological conditions in some eye diseases such as optic neuritis 17 and comitant strabismus. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Presumably, these latter regions are involved in visuomotor action and visuospatial attention, among other functions, which appear to be impaired in amblyopes ( Niechwiej-Szwedo et al, 2012 , Niechwiej-Szwedo et al, 2014 ). Two similar studies have now examined subjects with strabismic amblyopia and also find multiple sites of abnormality including lingual and inferior temporal cortex, as well as cerebellum, angular and cingulate and medial frontal cortex ( Huang et al, 2016 ; Tan et al, 2016 ). While these wide-ranging cortical effects are likely to result from the chronically impaired visual input experienced in visual cortex, none of these studies have actually defined the functional boundaries of individual visual areas or evaluated the connectivity between them.…”
Section: Introductionmentioning
confidence: 93%
“… 20 Another ReHo study demonstrated that persistent somatoform pain disorder was associated with dysfunction of brain activity in many regions. 21 In our previous studies, the ReHo method was successfully used to assess synchronous neural activities in some eye diseases such as optic neuritis, 22 comitant strabismus, 23 and acute open-globe injury. 24 …”
Section: Introductionmentioning
confidence: 99%